2015
DOI: 10.1515/cclm-2014-1047
|View full text |Cite
|
Sign up to set email alerts
|

Validation of CFTR intronic variants identified during cystic fibrosis population screening by a minigene splicing assay

Abstract: Hybrid minigenes assay are a simple and rapid tool to evaluate the effects of intronic variants without the need of analyzing patient's mRNA, and are particularly suited to analyze variants identified during population screenings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…12 As no patient's RNA was available, to confirm its pathogenicity, we functionally characterized the synonymous variant using a β-globin hybrid minigene assay, which has been effectively used to validate potential splicing variants (Figure 2c). 13 RT-PCR analysis from cells transfected with the mutant construct showed an aberrant splicing compared with controls and yielded two bands (Figure 2d): sequencing of the lower fragment revealed that it corresponds to shorter transcripts owing to the activation of a novel canonical AG/GT 5′ donor splice site within SF3B4 exon 3 and the use of two different AG acceptor sites (the first in position c.536_537, the second three nucleotides downstream) (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…12 As no patient's RNA was available, to confirm its pathogenicity, we functionally characterized the synonymous variant using a β-globin hybrid minigene assay, which has been effectively used to validate potential splicing variants (Figure 2c). 13 RT-PCR analysis from cells transfected with the mutant construct showed an aberrant splicing compared with controls and yielded two bands (Figure 2d): sequencing of the lower fragment revealed that it corresponds to shorter transcripts owing to the activation of a novel canonical AG/GT 5′ donor splice site within SF3B4 exon 3 and the use of two different AG acceptor sites (the first in position c.536_537, the second three nucleotides downstream) (Figure 2e).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, genetic variants mapping to exons of a lincRNA may alter the lincRNA secondary structure, which can be partly predicted using RNAfold web server (Hofacker and Stadler, 2006). The 5 UTR (un-translated region) variants may affect the process of splicing and stability of RNA conformation, a functional splicing reporter minigene assay should be used to assess the effect of genetic variants on RNA splicing (Giorgi et al, 2015). Through the aforementioned knowable strategies, comprehensive functional verification of non-coding variants is very important to understand their biological consequence; there is an urgent need to explore more practical methods and strategies for functional verification research.…”
Section: Function Verificationmentioning
confidence: 99%
“…Mis-regulation of splicing is associated with an increasing number of human pathologies, including neurodegenerative disorders, cancer and genetic diseases [ 13 ]. The minigene approach is able to detect mRNA splicing aberrations using cells that do not express the endogenous mRNA and is a powerful and simple molecular tool to analyze mutations that might affect splicing [ 14 , 15 , 16 , 17 ]. Here, we report two Chinese patients suffering from seizures who were found to have DHP deficiency caused by novel heterozygous DPYS mutations.…”
Section: Introductionmentioning
confidence: 99%